KOMITMEN ORGANISASI DITINJAU DARI TIPE KEPRIBADIAN BIG FIVE PADA ANGGOTA KEPOLISIAN BIDKEU POLDA JAWA TENGAH - Illuminata Rheny; Linda Putri Fatiyan (IMAGE, 2022)
The purpose of this study was to determine the personality correlation of the Big Five from Organizational Commitment which was reviewed by members of the Central Java Regional Police Bidkeu Police. The sample used in the study was members of the Central Java Regional Police Bidkeu with a total of 92 people. Analysis of the data used Speraman correlation coefficient is a nonparametric statistic. This statistic is a measure of association or relationship that can be used in the condition that one or both of the variables measured are on an ordinal scale but the norm conditions are not met. Based on the results of the study, the hypothesis which states "There is a correlation between the Big Five Personality Types and Organizational Commitment to Members of the Central Java Regional Police Bidkeu Police", can be accepted. This is indicated by a significant value of 0.000 which means that the Big Five personality type variable has a significant effect on Organizational Commitment.